1977
DOI: 10.1128/aac.11.3.427
|View full text |Cite
|
Sign up to set email alerts
|

Cefoxitin: Clinical Evaluation in Thirty-Eight Patients

Abstract: Clinical and bacteriological efficacy, patient tolerance, and toxicity of cefoxitin, a beta-lactamase-resistant cephamycin, were evaluated in 38 patients; 13 had soft tissue infection, 12 had pneumonia, 3 had urinary tract infection, 2 had peritonitis, and 4 had miscellaneous infections. In five patients, infection was clinically evident, though not bacteriologically proven. The latter patients were evaluated with regard to tolerance and toxicity only. Among the 34 infections in 33 patients, 71% were considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 16 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…Results of recent clinical trials in adult patients have shown that a variety of acute infections with S. aureus, S. pyogenes, S. pneumoniae, and H. influenzae (7,8,10,11) could be treated successfully with cefoxitin. A low incidence of drug-associated adverse reactions was reported in these studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Results of recent clinical trials in adult patients have shown that a variety of acute infections with S. aureus, S. pyogenes, S. pneumoniae, and H. influenzae (7,8,10,11) could be treated successfully with cefoxitin. A low incidence of drug-associated adverse reactions was reported in these studies.…”
mentioning
confidence: 99%
“…Preliminary data indicate that cefoxitin is safe and effective in children (9). Although the pharmacokinetics of cefoxitin have been studied in adults (5,8,11) Serum concentrations were plotted against time, using a semi-logarithmic scale. The serum half-life was calculated when blood levels were declining exponentially during the elimination phase.…”
mentioning
confidence: 99%
“…otic, has been effective and well tolerated in adults with infections due to susceptible bacteria (3)(4)(5). Its antimicrobial spectrum of activity, which includes gram-positive cocci and Haemophilus influenzae, makes it a potentially useful drug for the parenteral treatment of serious infections in children, which are most often due to these organisms (2) By using the criteria of disk zone size -18 mm and miniimum inhibitory concentration s 16 yg/ml, all of the organisms recovered were susceptible to cefoxitin by the disk diffusion or broth dilution method or both.…”
mentioning
confidence: 99%
“…Cefoxitin is a semisynthetic cefamycin, active in vitro against common meningeal pathogens such as Neisseria meningitidis, Streptococcus pneumoniae, and ampicillin-susceptible and -resistant strains of Haemophilus influenzae type b (1,2,6,8,14,17). The results of clinical trials in adults (6,12,13) and children (2,8) have shown that this drug is safe and effective against infections with S. pneumoniae and H. influenzae b outside the central nervous system.…”
mentioning
confidence: 99%
“…The results of clinical trials in adults (6,12,13) and children (2,8) have shown that this drug is safe and effective against infections with S. pneumoniae and H. influenzae b outside the central nervous system. Thus, cefoxitin has the potential for single-drug therapy for infants and children with suspected bacterial meningitis provided it effectively penetrates into the cerebrospinal fluid (CSF).…”
mentioning
confidence: 99%